Natural radioelements concentration analysis and risk assessment in drinking water of mining area Niger State, North Central Nigeria - Muhammad, Abdullahi; Abbasi, Akbar (Taylor & Francis Inc, 2025)
In this study, gamma spectrometry analysis was performed to determine the activity concentration of 40K,226Ra, and 232Th in four different water sources in three different communities (Shakwata, Eregi, and Pina) in Niger State, north-central Nigeria. Total 20 water samples were analyzed. The activity concentration of 40K,226Ra, and 232Th in the water ranged from 0.35 +/- 0.03 to 33.28 +/- 2.97 Bq l-1, 1.32 +/- 0.07 l-1 to 3.06 +/- 0.18 Bq l-1, and 0.85 +/- 0.14 to 2.41 +/- 0.15 Bq l-1, respectively. For all five age groups, the annual effective dose from radionuclide intake in water sources across the three communities exceeded recommended limits, except in sample locations SW1, SW2, SW3, SW6, PWVI, and PWVII between the ages of 2-7 years and 7-12 years, where the 232Th level was found to be below the recommended limit of 1.0 mSv y-1 set by ICRP. Therefore, considering that the annual effective dose exceeds the WHO and ICRP recommended guidelines, the water sources from the mining areas should be restricted to domestic use and not for public consumption except after treatment.
Keywords: Activity concentration; annual effective dose; gamma-ray spectrometry; Niger State; radiotoxicity